2016
DOI: 10.1038/eye.2016.41
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal anti-vascular endothelial growth factor combined with half-fluence photodynamic therapy for choroidal neovascularization in chronic central serous chorioretinopathy

Abstract: Purpose To evaluate the results of indocyanine green angiography (ICGA)-guided verteporfin photodynamic therapy (PDT) with half-fluence rate combined with intravitreal application of anti-VEGF in treating choroidal neovascularization (CNV) in chronic central serous chorioretinopathy (CSCR). Patients and methods In this retrospective cohort study 17 consecutive patients with secondary CNV due to chronic CSCR had their diagnosis verified with fluorescein angiography (FA) and ICGA at baseline. All eyes received e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 36 publications
1
16
0
1
Order By: Relevance
“…This is the score provided by the computerized adaptation of the ETDRS method . To use this system with the standard ETDRS chart with five letters per line, you need to either measure VA at a non‐standard 1 m (for patients with poor VA) or measure VA at the standard 4 m and add 30 letters to the number of letters read . This is clearly understood by researchers using the system in wet AMD studies, but the system is now permeating into standard clinics and confusion abounds.…”
Section: Confusion 5 Number Of Letters Readmentioning
confidence: 99%
“…This is the score provided by the computerized adaptation of the ETDRS method . To use this system with the standard ETDRS chart with five letters per line, you need to either measure VA at a non‐standard 1 m (for patients with poor VA) or measure VA at the standard 4 m and add 30 letters to the number of letters read . This is clearly understood by researchers using the system in wet AMD studies, but the system is now permeating into standard clinics and confusion abounds.…”
Section: Confusion 5 Number Of Letters Readmentioning
confidence: 99%
“… 16 Inoue et al 19 have also shown that intravitreal bevacizumab is well tolerated in maintaining vision and reducing serous retinal detachment in chronic CSC, even 1 year after treatment. Smretschnig et al 20 also found efficacy of this combined approach for chronic CSC in treatment-naive cases associated with definitive CNV. As noted earlier, we did not see definitive CNV in each case reported in this study.…”
Section: Discussionmentioning
confidence: 92%
“…Good functional results were seen for CSC-related CNV in particular [52,53]. Combining PDT with a VEGF inhibitor could potentially also be beneficial in this setting [54]. However, there are no large studies in this regard to date.…”
Section: Photodynamic Therapymentioning
confidence: 99%